Pemberian Terapi Rebusan Daun Alpukat terhadap Penurunan Tekanan Darah Penderita Hipertensi - Juli Andri; Padila Padila; Ramadhan Trybahari Sugiharno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of the decoction of avocado leaves on reducing blood pressure in hypertensive patients in the Working Area of the West Lingkar Health Center in Bengkulu City. This type of research is a quasi-experiment with a two-group pre-test and post-test design. The results showed that the average systolic blood pressure before avocado leaf decoction was 143.27 mmHg with SD. 6,497, meaning that systolic blood pressure is included in the category of hypertension level 1. The average diastolic blood pressure before the avocado leaf decoction intervention was 84.33 mmHg with SD—4,865, where diastolic blood pressure is included in the prehypertension category. The bivariate analysis results showed that the p-value for systolic blood pressure was 0.000, and the p-value for diastolic blood pressure was 0.000. In conclusion, there was a significant effect between giving avocado leaf decoction intervention before and after reducing blood pressure. Keywords: Hypertension, Avocado Leaf Decoction, Blood Pressure